Generation of Glioblastoma specific SNAP based antibody fusion proteins for future radiolabelling application - Mayuni, Grace (Adolescent Health Research Institute, 2024)
Each year, Central Nervous System (CNS) cancers affect about 300,000 individuals globally, accounting for 1-2% of all adult cancer cases. Despite being rare, CNS cancers reportedly have disproportionately high morbidity and mortality rates compared to their incidence. Globally, Glioblastoma Multiforme (GBM) is the most aggressive CNS malignancy, accounting for 45% of brain tumours, with less than 5% of patients surviving for more than 5 years. To date, complete surgical resection followed by adjuvant chemotherapy and/or radiotherapy has been the standard of care treatment. This has been shown to not be curative, as it can only slightly improve prognosis and increase patient survival from 3–4 months to 14–16 months after diagnosis. However, it has been noted that early diagnosis increases the chance of patients going into complete remission following early treatment. Unfortunately, current methods of diagnosing GBM are very invasive and imprecise, necessitating more targeted, and more reliable diagnostic techniques. The use of antibody-based targeted agents in GBM treatment is being advanced due to their ability to specifically differentiate tumour masses from healthy tissue. The success of antibody-based targeted approaches lies in the selection of biomarkers that are selectively found in tumour cell populations. One type of biomarker is known as tumour-associated antigens (TAAs), which are antigenic substances present at a much relatively lower incidence on normal cells but highly correlated with certain tumour cells. The focus of this study was on two TAAs that have been established as being overexpressed in GBM: (i) the transmembrane protein epidermal growth factor receptor (EGFR), which is associated with tumour cell proliferation, and (ii) Fibroblast Activation Protein alpha (FAPα), an active protease in the stromal tissue of the GBM tumour microenvironment. SNAP-tag® fusion antibodies against the abovementioned TAAs were employed in this study. The fusion antibody is a recombinant antibody-based fusion protein created by fusing the SNAPtag®, a modified version of the DNA repair enzyme O6 -alkylguanine DNA alkyltransferase (hAGT), to a single chain variable fragment (scFv) region of an antibody, thereby providing a tool that can detect and label TAAs. The SNAP-tag® element is engineered to irreversibly react with any benzylguanine (BG) substrates, including labelling dyes or toxins, with a controlled 1:1 Masters Thesis 14 Grace Mayuni stoichiometry. According to previous studies, SNAP-tag fusion proteins have exhibited strong cytotoxic profiles as an immunotherapeutic tool as well as good imaging profiles as an immunodiagnostic tool. In this study, the recombinant SNAP fusion proteins, anti-FAPα (scFv)-SNAP and anti-EGFR (scFv)-SNAP were transiently expressed in mammalian cell culture. The recombinant protein was purified from harvested cell culture supernatant using immobilized metal ion affinity chromatography (IMAC). The enzymatic activity of the SNAP-tag element was tested using BGmodified fluorophores. To characterize highly specific in vitro labelling, the SNAP-tag-based fusion proteins were conjugated to BG-Alexa Fluor 647 to generate an immunofluorescent protein that can label TAAs in live tumour cells. To characterize the immunotherapeutic activity, the SNAP-tag fusion proteins were conjugated to the small molecule toxin, BG-Auristatin F, to generate an ADC that can kill TAA-expressing cells in vitro. Anti-FAPα (scFv)-SNAP and anti-EGFR (scFv)-SNAP fusion proteins were successfully expressed in this study with sufficient yields for small-scale purification. Through a series of selflabelling experiments with the BG-modified fluorophores, BG-Alexa Fluor 488 and BG-Alexa Fluor 647, the enzymatic activity of the SNAP-tag element of each construct was confirmed. The optimal binding ratio of fusion protein: BG-substrate conjugate for downstream experiments was determined to be 1:1. Using live cell imaging, the biological functionality of the fusion protein construct through site-specific labelling on antigen-expressing cell lines was demonstrated. Finally, this study investigated the cytotoxicity of SNAP-fusion proteins conjugated to toxic payloads. Using a cell proliferation assay, the next-generation ADC, anti-EGFR (scFv) SNAPAURIF, was tested and validated for its cell-killing activity. This ADC was able to elicit high rates of killing, exhibiting IC50 values in nanomolar ranges in three different antigen-positive tumour cell lines, with no cytotoxicity observed in the antigen-negative tumour cell lines. The targeted activity of this recombinant SNAP fusion protein format validates its biological function, making it suitable for further preclinical investigation. This study aimed to characterize SNAP fusion proteins that can target GBM-specific TAAs. It successfully demonstrated the optimal conjugation efficiencies and validated the site-specific targeted activity of the scFv SNAP fusion antibody format. This work serves as a proof-of-concept Masters Thesis 15 Grace Mayuni towards investigating the use of radio-labelled SNAP-tag-based antibody fusion proteins in GBM tumour detection and patient stratification to offer personalized therapeutics.